Exploring novel infusion regimens of phenylephrine during spinal anesthesia for caesarean delivery: The effects on hemodynamic control and fetal acid-base status - Syed N Muzaffar; Kajal Jain; Sukhen Samanta; Neerja Bhardwaj; Praveen Kumar (Wolters Kluwer Medknow Publications, 2016)
Background: A renewed interest has emerged in the use of bolus or intravenous (IV) infusion of phenylephrine for management of hypotension during spinal anesthesia (SA) for caesarean section to achieve optimal maternal and neonatal outcome. The aim of our study was to investigate the efficacy of using three different phenylephrine infusion regimens to maintain maternal baseline blood pressure during SA for caesarean delivery. Materials and Methods: Ninety parturients undergoing SA for elective caesarean delivery received an IV infusion of phenylephrine in one of three different concentration ratios. The groups contained a potency equivalent of 100 μg/min, 80μg/min, and 60 μg/min infusion doses. The infusions were adjusted to maintain systolic blood pressure (SBP) near the baseline until uterine incision. Hemodynamic changes in mother and umbilical cord blood gases were compared. Results: As concentration of phenylephrine increased, following significant trends were noticed: in group A, 10/29 (34.5%) patients had hypotension as compared to 2/28 (7.4%) patients in group B and 4/28 (14.3%) patients in group C. On the other hand, we found that the incidence of hypertension and bradycardia was higher in groups B (22/28; 4/28) and C (26/28; 10/28) as compared to those in group A (3/29; 2/29), respectively. Neonatal acid-base status in all three groups was favorable. Conclusions: As the concentration of phenylephrine increased, the tendency for SBP to be above the baseline increased, along with an incidence of bradycardia. Therefore, we conclude that low dose infusion regimens of phenylephrine, i.e. between 60 μg/min and 80 μg/min, will be more effective in prevention of hypotension during SA for caesarean delivery.